Blood Progenitor Cell Mobilization Driven by TWEAK Promotes Neovascularization and Reduces Brain Damage in a Rat Model of Intracerebral Hemorrhage - Daniel Romaus-Sanjurjo; Esteban López-Arias; Cristina Rodríguez; Pablo Hervella; Mariña Rodríguez-Arrizabalaga; Manuel Debasa-Mouce; Juan Manuel Pías-Peleteiro; Ramón Iglesias-Rey; Pablo Aguiar; Ángeles Almeida; José Castillo; Alberto Ouro; et al. (Antioxidants)
Non-traumatic intracerebral hemorrhage (ICH) is one of the most devastating and disabling forms of stroke; however, there are no effective pharmacological therapies available following the insult. Angiogenesis appears as a key step to overcoming the damage and promoting functional recovery. In this context, endothelial progenitor cells (EPCs) mobilization improves oxidative stress and promotes neovascularization, which has been linked to beneficial outcomes following both ischemic and hemorrhagic stroke. The TNF-like weak inducer of apoptosis (TWEAK), binding to its receptor Fn14, has been suggested as an inducer of EPCs differentiation, viability and migration to the injury site in a model of myocardial infarction. Here, we have performed a proof-of-concept preclinical study in a rat model of ICH where we report that a 50 μg/kg dose of rat recombinant TWEAK (rTWEAK) promotes blood progenitor cells mobilization, mainly EPCs. As soon as 72 h post-injury, brain neovascularization, and, importantly, long-term hematoma reduction and improved functional recovery is reported. In contrast, a higher dose of 150 μg/kg blocked those beneficial outcomes. Therefore, a low dose of rTWEAK treatment promotes neovascularization and reduces brain damage in a rat model of ICH. Further clinical studies will be needed to demonstrate if rTWEAK could represent a new strategy to promote recovery following ICH.